Loading

To find the gradient of any curve, we take the derivative. So in this case, we need to take dy/dx. We do this by multiplying the term by the power on x, and then lowering the power by one. For example, for the first term, x^{4}, the power is four, so we multiply x^{4} by four, and the power becomes three, so we have 4x^{3}. We repeat this for all of the terms individually to get dy/dx = 4x^{3 }-16x +60. That gives us the gradient at any point. To get the gradient at x = 6 we need to substitute the value in to the new equation, so we get dy/dx = 4 * 6^{3} - 16 * 6 + 60 = 828

Differentiate f(x) = 14*(x^2)*(e^(x^2))

Answered by Toby C.

Integrate x^2 + 2x + 5x^-1

Answered by John A.

Solve the equation 2log (base 3)(x) - log (base 3)(x+4) = 2

Answered by Theranjit S.

Given that A(sin θ + cos θ) + B(cos θ − sin θ) ≡ 4 sin θ, find the values of the constants A and B.

Answered by David B.